Semito-Hamitic or Afro-Asiatic consonantism and lexicon: Episodes of a comparative research I (Part 2: Marcel Cohen’s Essai comparatif) - Takács, Gábor (Lingua Posnaniensis, 2023)
A retrospective account on past comparative research on Afro-Asiatic (AA) or Semito-Hamitic / Hamito-Semitic (SH / HS, resp.) phonology (first of all consonantism, also root structure) and lexicon, segmented into episodes according to diverse (often overlapping in time) trends is now under way and will be presented part by part in a series of papers. The present paper contains the first ever direction of this research, labelled “Semito-Hamitology” covering studies seeking, in their conception, the “African”, i.e. “Hamitic” kinship of Semitic.